Dental Management of Hypophosphatemic Vitamin D Resistant Rickets - Akif Demirel; Ayşe Tuba Altuğ; Esra Erdemli; Firdevs Tulga Öz (Galenos Yayinevi, 2018)
Vitamin D-Resistant Rickets (VDRR) is an X-linked disease, causing mineralization disturbances of hard tissues such as bones and deciduous and permanent dentition. The dental findings of VDRR are enlarged pulp horns and chambers, defective enamel/dentin tissue, pulpitis, pulp necrosis, periapical recurrent abscesses and periapical complications without dental caries or trauma. The treatment options of this condition are extraction, endodontic approaches such as pulpotomy/pulpectomy, restorative and preventive applications. The aim of this case report is to summarize the dental clinical, radiographical, histopathological findings and treatment options of VDRR in a 4.5-year-old girl.